Discovering Computers Digital Technology, Data, and Devices - Campbell, Jennifer T. (The Shelly Cashman Series, 2023)
Discovering Computers: Digital Technology, Data, and Devices, 17th edition, teaches you not only the basics of technology, but also how you will use it -- and the responsibilities that go along with being a digital citizen. Focusing on current technology, the content addresses convergence of devices and platforms. Each module integrates practical how-to tips, ethics issues and security topics, while Consider This boxes woven throughout help you sharpen your critical-thinking skills. A variety of end-of-module activities -- checkpoint questions, small group activities and problem-solving exercises -- enable you to put what you learn into practice. MindTap digital learning solution is also available. Using an inviting approach that ensures understanding, DISCOVERING COMPUTERS equips you with the information you need for success at home, school and work.